Hypersensitivity to local anesthetics. - Mascarenhas, Maria Isabel (2011)
Local anesthetics (LA) are frequently used in medical and surgical and dental procedures. Adverse reactions to LA are rare, and hypersensitivity reactions are very rare. Nevertheless, they are the third more frequent cause of referral to Allergy Clinics due to drug allergy, after betalactamic antibiotics and non-steroidal anti-inflammatory agents. In this paper we review hypersensitivity reactions to LA and propose a diagnostic approach to them.